Exploring Student’s Blended Learning through Social Media - Leon Andretti Abdillah (ComTech: Computer, Mathematics and Engineering Applications, 2016)
Information technology (IT) has been used widely in many aspects of our daily life. Social media as a leading application on the internet has changed many aspects of life become more globalized. This article discussed the use of social media to support learning activities for students in the faculty of computer science. The author used Facebook and WordPress as an alternative to electronic learning, those were: 1) online attendance tool, 2) media storage and dissemination of course materials, 3) and event scheduling for the lectures. Social media succeed to change the way of modern learning styles and environment. The results of this study are some learning activities such as (1) Preparation, (2) Weekly meeting activities, (3) Course Page, (4) Social Media as Online Attendance Tool, (5) Social Media as Learning Repository and Dissemination, and (6) Social Media as Online Event Scheduling. Change conventional learning model becomes visual and distanceless.